2006
DOI: 10.1021/ac0612877
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Solubilization, Structural Change, and Functional Conversion of Cytochrome c in Ionic Liquids via Crown Ether Complexation

Abstract: This article reports on the extraction behavior of heme proteins from an aqueous phase into ionic liquids (ILs) with dicyclohexano-18-crown-6 (DCH18C6), and the structure-function relationship of cytochrome c (Cyt-c) dissolved in ILs. We have found that DCH18C6 enables transfer of Lys-rich proteins into ILs via supramolecular complexation. The hydrophobicity and functional groups of ILs have a great influence on protein partitioning, and a hydroxyl group-containing IL with DCH18C6 is capable of the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 62 publications
2
72
2
2
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Among many possibilities of applying ionic liquids, IL-water (W) two-phase systems that consist of an aqueous or a nonpolar molecular solvent and an ionic liquid are of considerable relevance with analytical chemistry and separation technology. A direct application of IL-W two-phase systems is the extraction of neutral compounds of relatively low molecular weights, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] biopolymers 44,[48][49][50][51] and ions. Several reviews on extraction with ILs are available.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Among many possibilities of applying ionic liquids, IL-water (W) two-phase systems that consist of an aqueous or a nonpolar molecular solvent and an ionic liquid are of considerable relevance with analytical chemistry and separation technology. A direct application of IL-W two-phase systems is the extraction of neutral compounds of relatively low molecular weights, [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] biopolymers 44,[48][49][50][51] and ions. Several reviews on extraction with ILs are available.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the conventional organic solvents, ILs enabled quantitative recovery of amino acids and eliminated emulsion formation, which usually occurs when cationic or anionic extractants are used. Shimojo et al (Shimojo et al, 2006a;Shimojo et al, 2006b) investigated a hydroxyl-groupcontaining IL with DCH18C6 was capable of quantitative partitioning of heme protein cytochrome c (Cyt-c) via supramolecular complexation and that the resulting Cyt-c-DCH18C6 complex acts as a homogeneous biocatalyst in ILs. While using conventional organic solvents the protein transfer was negligibly small.…”
Section: Effects Of Ionic Liquids On the Formation Of The Supramolecumentioning
confidence: 99%
“…In a similar manner, 18-crown-6 recognizes also the protonated primary amino groups of a protein, resulting in the formation of a supramolecular complex between the crown ether molecules and the protein [19][20][21][22]. Recently, extraction of a cationic protein cytochrome c into an ionic liquid using a crown ether as the extractant has been accomplished [23,24]. Similarly, we recently found that the extraction behavior of cytochrome c is influenced by adding a crown ether as the ligand in the Li 2 SO 4 (lithium sulfate)/PEG ATPS [25].…”
Section: Solvent Extraction Research and Development Japan Vol 17mentioning
confidence: 99%